Single-cell transcriptomics of the Drosophila ring gland identifies the SoxN–Vvl complex as a key regulator of juvenile hormone biosynthesis - Yuhan Luo; Nan Chen; Yue Gao; Wei Luo; Shanshan Liu; Yang Li; Hanyue Wang; Xiangbin Gao; Jiawei Chen; Haosheng Ye; Kirst King-Jones; Subba Reddy Palli; et al. (Proceedings of the National Academy of Sciences, 2026)
Juvenile hormone (JH) is essential for maintaining juvenile status and promoting reproduction in insects, yet the transcriptional regulation of JH biosynthesis remains poorly understood. Previous transcriptomic studies of the Drosophila ring gland—which is composed of the corpus allatum (CA), prothoracic gland (PG), and corpora cardiaca (CC)—have treated the ring gland as a single tissue. As a result, these approaches lacked the resolution necessary to dissect JH biosynthesis and its regulation in a cell-type-specific manner. To overcome this limitation, we performed single-cell RNA sequencing (scRNA-seq) of 7,919 cells isolated from the larval ring glands. This analysis resolved distinct transcriptional profiles for the CA, PG, and CC, and enabled the identification of CA-specific transcription factors. Among them, SoxNeuro (SoxN), was found to be essential for JH biosynthesis and functionally important for both metamorphosis and reproduction. We further demonstrate that SoxN physically interacts with Ventral veins lacking (Vvl) to form a transcriptional complex that directly regulates Jhamt , a rate-limiting enzyme in JH biosynthesis, via a defined promoter region. Together, this work presents a single-cell transcriptomic atlas of the Drosophila ring gland and identifies the SoxN–Vvl complex as a critical regulator of JH biosynthesis, offering insight into the transcriptional control of insect endocrine function.